1977
DOI: 10.1007/bf00121548
|View full text |Cite
|
Sign up to set email alerts
|

The sequencing of instruction and the concept of assimilation-to-schema

Abstract: The concept of assimilation-to-schema proposes that learning depends on three conditions: (1) the reception of the to-be4earned material, (2)the availability of a cognitive structure to which the new material may be assimilated, (3) the activation of the structure during learning. The concept provides weak (i.e., concerning amount of learning) and strong (i.e. concerning the structure of learning outcomes) predictions with respect to the effects of sequencing of instruction, ordering of instruction and organiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

1979
1979
2008
2008

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 68 publications
(58 reference statements)
1
29
0
Order By: Relevance
“…First, a computerized data retrieval search was conducted using the ERIC data base; the search located all papers in the data base which contained the word "advance organizer" (or "advanced organizer") in the title, abstract or as a descriptor. Second, the relevant bibliographic portions of several recent reviews on advance organizers were included (Ausubel, 1962(Ausubel, , 1968(Ausubel, , 1977Barnes and Clawson, 1975;Barron, 1972;Blanton, 1972;Hansell, 1976;Hartley and Davies, 1976;Koran et al, 1975;Lawton and Wanska, 1977;Lesh, 1976a;Mayer, 1977a;Novak et al, 1971;Ring and Novak, 1971;Vacca, 1977). In addition, for each paper located in the first two steps its reference list was examined for citations of additional advance organizer studies.…”
Section: Scope Of This Reviewmentioning
confidence: 99%
“…First, a computerized data retrieval search was conducted using the ERIC data base; the search located all papers in the data base which contained the word "advance organizer" (or "advanced organizer") in the title, abstract or as a descriptor. Second, the relevant bibliographic portions of several recent reviews on advance organizers were included (Ausubel, 1962(Ausubel, , 1968(Ausubel, , 1977Barnes and Clawson, 1975;Barron, 1972;Blanton, 1972;Hansell, 1976;Hartley and Davies, 1976;Koran et al, 1975;Lawton and Wanska, 1977;Lesh, 1976a;Mayer, 1977a;Novak et al, 1971;Ring and Novak, 1971;Vacca, 1977). In addition, for each paper located in the first two steps its reference list was examined for citations of additional advance organizer studies.…”
Section: Scope Of This Reviewmentioning
confidence: 99%
“…As Mayer's (1977) review has indicated, the use of assimilation-toschema descriptions of learning has proven particularly useful for prescribing instructional methods and predicting differences due to instruction in terms of distinct learning outcomes. Cognitive/information processing models of data structures and descriptions of modes of learning such as those by Rumelhart and Norman (1976) have provided a rich environment for expanding upon earlier, related work by Ausubel and others on advanced organizers.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to research conducted by Ausubel and his coworkers (Ausubel, 1960;Ausubel and Fitzgerald, 1962;Ausubel and Youssef, 1963;Fitzgerald and Ausubel, 1963), Mayer (1977) has conducted a major review of work by Bransford and Johnson (1972), Dooling and Lachman (1971), Dooling and Mullet (1973), Mayer (1975), and others on the role of advanced organizers and sequencing of instruction as variables effecting the assimilation of instructional material to a learner's schema. Mayer has concluded that what may appear to be inconsistent findings in instructional sequencing research may be best understood in terms of the internal state of the learner.…”
Section: Data Structures and Instructionmentioning
confidence: 99%
“…These include: Presenting examples before or after presenting a solution rule (see the review by Hermann, 1969); presenting general concepts before or after detailed information (McDade, 1978); and presenting a concrete model before or after abstract text (Mayer, 1977). A sequencing effect might be expected to occur in the situation under investigation, since similar factors appear to be involved in the Theory-to-application/Application-to-theory distinction.…”
Section: Sequence Of Instructionmentioning
confidence: 99%